2008
DOI: 10.1111/j.1524-6175.2007.08145.x
|View full text |Cite
|
Sign up to set email alerts
|

Prompt, Aggressive BP Lowering in High‐Risk Patients

Abstract: Various populations with hypertension have been singled out by current treatment guidelines as requiring more specific treatment. These include patients with stage 2 hypertension, black patients, and patients with coexistent diabetes mellitus and coronary heart disease. Hypertension in these groups is often associated with higher risk of cardiovascular morbidity and mortality. This article reviews current knowledge regarding hypertension in high-risk patient populations, with a particular focus on the importan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 69 publications
0
9
0
Order By: Relevance
“…Prompt BP control is an important goal for antihypertensive therapy, as recent clinical trials have suggested that the time taken for treatment effects to occur is an important factor in reducing cardiovascular risk. 21,22 Indeed, the results of the VALUE (Valsartan Antihypertensive Long-Term Use Evaluation) study suggest that more rapid initial reductions in BP are associated with improved long-term patient outcomes. 23,24 The finding of a recent medical records database analysis that only about 50% of patients with stage 2 hypertension achieved BP control within 1 year of starting antihypertensive therapy 25 highlights the need for new options that can achieve more rapid BP control in this patient group.…”
Section: Discussionmentioning
confidence: 96%
“…Prompt BP control is an important goal for antihypertensive therapy, as recent clinical trials have suggested that the time taken for treatment effects to occur is an important factor in reducing cardiovascular risk. 21,22 Indeed, the results of the VALUE (Valsartan Antihypertensive Long-Term Use Evaluation) study suggest that more rapid initial reductions in BP are associated with improved long-term patient outcomes. 23,24 The finding of a recent medical records database analysis that only about 50% of patients with stage 2 hypertension achieved BP control within 1 year of starting antihypertensive therapy 25 highlights the need for new options that can achieve more rapid BP control in this patient group.…”
Section: Discussionmentioning
confidence: 96%
“…Lower goals for blood pressure management have been suggested for highrisk individuals. 31 Also for serum cholesterol levels, an aggressive and intensified treatment has been shown to be beneficial in patients at risk. 32 For diabetic patients, an intensive personalized treatment is beneficial, but not for high-risk individuals in particular.…”
Section: Clinical Implications and Interventionsmentioning
confidence: 99%
“…In a recent meta-analysis, however, adding an ARB to an ACEI showed only modest effects (5/3 mm Hg) on BP [ 32 ]. When an ARB was added to an ACEI in the early phases after myocardial infarction, a signifi cant increase was noted in side effects in terms of hypotension and renal dysfunction, with no evidence of clinical benefi ts [ 31 ]. In contrast, adding ARBs to ACEIs reduced cardiovascular morbidity and mortality in patients with congestive heart failure [ 33 ].…”
Section: Current American Heart Association Guidelinesmentioning
confidence: 93%
“…Angiotensin receptor blockers (ARBs) were shown to have cardiovascular benefi t similar to ACEIs in patients with congestive heart failure or previous myocardial infarction, and thus should be used in patients who cannot tolerate ACEIs [ 31 ]. In a recent meta-analysis, however, adding an ARB to an ACEI showed only modest effects (5/3 mm Hg) on BP [ 32 ].…”
Section: Current American Heart Association Guidelinesmentioning
confidence: 98%